Institutionalizing Social Entrepreneurship in Pesantren Business Units: A Qualitative Study of Sustainable Community Empowerment in East Java - Muhammad Hafidh Nashrullah; Ahmad Munir Hamid; Nawari; Ishfaq Ahmed (ADILLA : Jurnal Ilmiah Ekonomi Syari'ah, 2026)
This study examines the institutionalization of social entrepreneurship within pesantren (Islamic boarding school) business units in East Java and its contribution to sustainable community empowerment. A qualitative multiple-case study approach was employed, using in-depth interviews, participant observation, and document analysis across five pesantren with established business units. The findings reveal that social entrepreneurship is institutionalized through the integration of Islamic values, local wisdom, and entrepreneurial practices. Visionary leadership, stakeholder collaboration, hybrid social-commercial strategies, and organizational learning emerge as the main institutional drivers. The study introduces the concept of Spiritual-Social Value Recoupling, describing how religious values reshape business practices to prioritize social welfare alongside economic sustainability. Despite challenges related to resource dependency, leadership succession, and mission drift, pesantren business units have generated multidimensional impacts, including economic empowerment, educational improvement, social welfare, and environmental responsibility. The findings enrich social entrepreneurship theory within faith-based organizations and provide practical insights for strengthening sustainable community development.